1970
DOI: 10.3329/jdmc.v18i2.6265
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors Associated with Stroke in Young Adults: A Prospective Study

Abstract: Objective: Stroke in young patients is not common. The purpose of this study was to find out the risk factors of stroke in young adults in Bangladesh and to compare with different other studies. Methods: 85 young adult cases of stroke patients with the age ranging from 14 to 45 years, admitted in different medical units of Dhaka Medical College Hospital from January 2008 to July 2009, were studied. The risk factors for stroke and the distribution of stroke types were analyzed. Results: The specific age group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…In this study hypertension was the most important risk factor of stroke, followed by smoking and diabetes mellitus, dyslipidaemia. Two previous Bangladeshi studies conducted by Siddique et al and Hossain also describes similar findings 14,16 . In a study done by Miah et al, reported that 78% of the stroke patients' required NG tube feeding for stroke 17 .…”
Section: Discussionsupporting
confidence: 74%
“…In this study hypertension was the most important risk factor of stroke, followed by smoking and diabetes mellitus, dyslipidaemia. Two previous Bangladeshi studies conducted by Siddique et al and Hossain also describes similar findings 14,16 . In a study done by Miah et al, reported that 78% of the stroke patients' required NG tube feeding for stroke 17 .…”
Section: Discussionsupporting
confidence: 74%
“…34 Hossain et al and Lipska et al also reported significant number of hyperlipidemic young strokes, 38% and 29% respectively. 15,17 Study in Iran, Pakistan and Srilanka showed a relative less prevalence of hyperlipidemia among young stroke. 9,14,35,36 A comparative study of ethnic South Asians and Whites in United Kingdom reported that the percentage of hyperlipidemic people was significantly higher among young South Asians.…”
Section: Hyperlipidemiamentioning
confidence: 99%
“…55 Figure 1 shows higher frequency of cardioembolism was present among young ischemic stroke patients of Hossain and Ghandehari. 15,19 Valvular heart diseases, including congenital and acquired, were the major findings in their studies. Other common sources of cardioembolism in young stroke were infective endocarditis, cardiomyopathy, myxoma, acute myocardial infarction, akinetic ventricular segment, etc ( Table 2).…”
Section: Cardioembolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of stroke here is 3 per 1000 above the age of 40 years 15 . We could find few similar studies involving stroke patients [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%